Occupations, ranks and kinship. Workers at the Santafé mint 1620- 1816 - Bonnett Vélez, Diana (Universidad Pedagógica y Tecnológica de Colombia, 2013)
The organization of the staff that worked at the Santafé Mint during its two characteristic periods is an aspect to be considered in order to understand the way theMint works, and the mentality about its administrative organization. These periods are inluenced by the relation ship between the Mint and the Crown. The irst periodwas between 1620 and 1753, and the second, from 1753 to 1816. This article will examine staff ranks in the Mint, along with workers’ hierarchicalization and functions.Likewise, in the irst period we will study the social and administrative origins of particular treasurers, kinship relationships and the problems caused by delegating jobs. Finally, we will refer to the conlicts and irregularities that led to organize several visits in order to maintain control over the civil servants in charge of the Mint.